Beyond the Alveolar Epithelium: Plasma Soluble Receptor for Advanced Glycation End Products Is Associated With Oxygenation Impairment, Mortality, and Extrapulmonary Organ Failure in Children With Acute Respiratory Distress Syndrome. Issue 5 (25th October 2021) - Lim, Michelle J.; Zinter, Matt S.; Chen, Lucia; Wong, Kayley Man Yee; Bhalla, Anoopindar; Gala, Kinisha; Guglielmo, Mona; Alkhouli, Mustafa; Huard, Leanna L.; Hanudel, Mark R.; Vangala, Sitaram; Schwingshackl, Andreas; et al.
Abstract : OBJECTIVES: Soluble receptor for advanced glycation end products is a known plasma marker of alveolar epithelial injury. However, RAGE is also expressed on cell types beyond the lung, and its activation leads to up-regulation of pro-inflammatory mediators. We sought to examine the relationship between plasma soluble receptor for advanced glycation end products and primary pulmonary dysfunction, extrapulmonary organ dysfunction, and mortality in pediatric acute respiratory distress syndrome patients at two early time points following acute respiratory distress syndrome diagnosis and compare these results to plasma surfactant protein-D, a marker of pure alveolar epithelial injury. DESIGN: Prospective observational study. SETTING: Five academic PICUs. PATIENTS: Two hundred fifty-eight pediatric patients 30 days to 18 years old meeting Berlin Criteria for acute respiratory distress syndrome. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Plasma was collected for soluble receptor for advanced glycation end products and surfactant protein-D measurements within 24 hours (day 1) and 48 to 72 hours (day 3) after acute respiratory distress syndrome diagnosis. Similar to surfactant protein-D, plasma soluble receptor for advanced glycation end products was associated with a higher oxygenation index ( p < 0.01) and worse lung injury score ( p < 0.001) at the time of acute respiratory distress syndrome diagnosis. However, unlike surfactant protein-D, plasma soluble receptor for advanced glycation end products was associated with worse extrapulmonary Pediatric Logistic Organ Dysfunction score during ICU stay (day 3; p < 0.01) and positively correlated with plasma levels of interleukin-6 ( p < 0.01), tumor necrosis factor-α ( p < 0.01), and angiopoietin-2 ( p < 0.01). Among children with indirect lung injury, plasma soluble receptor for advanced glycation end products was associated with mortality independent of age, sex, race, cancer/bone marrow transplant, and Pediatric Risk of Mortality score (day 3; odds ratio, 3.14; 95% CI, 1.46–6.75; p < 0.01). CONCLUSIONS: Unlike surfactant protein-D, which is primarily localized to the alveolar epithelium plasma soluble receptor for advanced glycation end products is systemically expressed and correlates with markers of inflammation, extrapulmonary multiple organ dysfunction, and death in pediatric acute respiratory distress syndrome with indirect lung injury. This suggests that unlike surfactant protein-D, soluble receptor for advanced glycation end products is a multifaceted marker of alveolar injury and increased inflammation and that receptor for advanced glycation end products activation may contribute to the pathogenesis of multiple organ failure among children with indirect acute respiratory distress syndrome.